Successful surgical management of hepatic alveolar echinococcosis by inductive therapy with albendazole – a case report - Bartels, Michael; Schmidt, Thomas; Lübbert, Christoph (Zeitschrift für Gastroenterologie, 2020)
We report the case of a 65-year-old female patient with hepatic alveolar echinococcosis (AE) caused by Echinococcus multilocularis. This infrequent zoonosis has a considerable morbidity and mortality. The malignant appearing hepatic mass was initially misdiagnosed as cholangiocarcinoma of the right hepatic lobe (segments VII, VIII, and IVa, sized 10.9 cm × 7.6 cm) involving the right and middle hepatic vein and extending close to the left hepatic vein. During exploratory laparotomy, the frozen-section biopsy was indicative of AE (World Health Organization [WHO] classification: stage P3N0M0). Due to the high operative risk, it was decided to pretreat the patient with albendazole as inductive therapy in order to remove the AE secondarily in accordance with the patient’s request. After year-long treatment with albendazole (under strict control of the maximum blood levels), a right hemihepatectomy was successfully performed. Postoperative treatment with albendazole had to be stopped prematurely after 11 months due to considerable subjective intolerance and a more-than-tenfold elevation of transaminases despite normal therapeutic albendazole blood levels. A 18F-FDG-PET/CT scan revealed no evidence of AE residues. Conducting follow-up examinations by 18F-FDG-PET/CT scans every 2 years is planned in order to recognize possible recurrence at an early stage.
Keywords: hepatic alveolar echinococcosis; Echinococcus multilocularis; inductive therapy; albendazole; surgical management